Profil Karakteristik dan Kecerdasan Majemuk Mahasiswa Fakultas Ilmu Pendidikan Berdasarkan Instrumen Multiple Intelligences Score - Tania Ramadhani; Soraya Hidayah; Elizabeth Parulian Pasaribu; Ella Pristiani; Dwitia Febriana Putri (CV. Eracita Grup, 2025)
This study aims to describe student characteristics and the multiple intelligences profile of students in the Faculty of Education at Universitas Negeri Medan based on the Multiple Intelligences Score (MIS). The study employed a quantitative method with a descriptive approach. The research subjects consisted of 25 students randomly selected from four study programs, namely Elementary School Teacher Education, Guidance and Counseling, Community Education, and Early Childhood Education. The research instruments included a student characteristics questionnaire and a multiple intelligences assessment based on the Multiple Intelligences Score (MIS), which is used to identify students’ tendencies across various types of intelligence. Data were analyzed using descriptive statistics, including frequency, percentage, and mean values, and were presented in the form of tables and infographics. The results showed that the majority of students were female and were within the age range of 18–21 years. The multiple intelligences profile revealed variations in intelligence types, with all intelligence categories appearing at different levels of dominance. Although several types of intelligence showed higher mean scores, no single intelligence dominated absolutely. These findings indicate that students’ intelligence profiles are heterogeneous and complementary. In conclusion, mapping student characteristics and multiple intelligences is essential as a basis for developing more adaptive learning strategies. It is recommended that educators and institutions consider the diversity of students’ intelligence profiles in designing instructional practices and academic support services.